2018
DOI: 10.3390/genes9100502
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into Date Palm Origins

Abstract: With the development of next-generation sequencing technology, the amount of date palm (Phoenix dactylifera L.) genomic data has grown rapidly and yielded new insights into this species and its origins. Here, we review advances in understanding of the evolutionary history of the date palm, with a particular emphasis on what has been learned from the analysis of genomic data. We first record current genomic resources available for date palm including genome assemblies and resequencing data. We discuss new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Phoenicia, a maritime trading nation occupying the coastal areas of modern northern Israel, Lebanon, and Syria (1500 to 300 BCE), was also historically associated with cultivation and trade of date palms (32). We can speculate that later west to east germplasm exchanges to this region may have been associated with domesticated varieties originating in Phoenician City States in North African (e.g., Carthage in present-day Tunisia) (32), where oasis agriculture appeared relatively late in the archaeological record (3).…”
Section: Discussionmentioning
confidence: 99%
“…Phoenicia, a maritime trading nation occupying the coastal areas of modern northern Israel, Lebanon, and Syria (1500 to 300 BCE), was also historically associated with cultivation and trade of date palms (32). We can speculate that later west to east germplasm exchanges to this region may have been associated with domesticated varieties originating in Phoenician City States in North African (e.g., Carthage in present-day Tunisia) (32), where oasis agriculture appeared relatively late in the archaeological record (3).…”
Section: Discussionmentioning
confidence: 99%
“…The subpopulations show strong distinction between North African (Western) and Arabian Gulf (Eastern) cultivars while admixture is observed in cultivars from Egypt, Sudan and the Middle East. High genetic diversity in the North Africa subpopulation argues against it simply a result of colonization from a middle-east population [8] though studies have shown a significant portion of the North Africa date palm genome likely originates from the Arabian Gulf date palm [3, 4, 10]. Despite these results, many have suggested that the date palm was originally domesticated in the region of modern day Iraq as the historical record of date palm is richest in that region [11].…”
Section: Introductionmentioning
confidence: 99%
“…Date palms were domesticated at least in the Persian Gulf region, followed by diffusion to North Africa (for review, Gros-Balthazard et al, 2018). A recent study, based on whole-genome re-sequencing data, indicated that North African date palms have been introgressed by the Aegean Phoenix theophrasti, and today, about 5-18% of their genome originates from this wild relative or a P. theophrasti-like population (Flowers et al, 2019).…”
Section: The Contribution Of P Theophrasti To North African Date Palmentioning
confidence: 99%
“…Date palms exist mostly as either cultivated or feral (i.e. uncultivated but derived from cultivated palms) domesticated forms (for review, Gros-Balthazard et al, 2018). Only a few relictual populations of its wild progenitor are known today in Oman (Gros-Balthazard et al, 2017), even though Tuaregs of the Tassili n'Ajjer (Algeria) consider it to be wild in their gardens (Battesti, 2004).…”
Section: Introductionmentioning
confidence: 99%